Prevalence of anti-HAV antibodies in multitransfused patients with beta-thalassemia - Siagris, Dimitrios (The WJG Press and Baishideng, 2008)
AIM: To detect the prevalence of anti-HAV IgG antibodies in adult multitransfused beta-thalassemic patients. METHODS: We studied 182 adult beta-thalassemic patients and 209 controls matched for age and sex from the same geographic area, at the same time. Anti-HAV IgG antibodies, viral markers of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection were evaluated. RESULTS: Anti-HAV IgG antibodies were detected more frequently in thalassemic patients (133/182; 73.1%) than in healthy controls (38/209; 18.2%, P < 0.0005). When we retrospectively evaluated the prevalence of anti-HAV IgG antibodies in 176/182 (96.7%) thalassemic patients, whose medical history was available for the previous ten years, it was found that 83 (47.2%) of them were continuously anti-HAV IgG positive, 16 (9.1%) acquired anti-HAV IgG antibody during the previous ten years, 49 (27.8%) presented anti-HAV positivity intermittently and 28 (15.9%) were anti-HAV negative continuously. CONCLUSION: Multitransfused adult beta-thalassemic patients present higher frequency of anti-HAV IgG antibodies than normal population of the same geographic area. This difference is difficult to explain, but it can be attributed to the higher vulnerability of thalassemics to HAV infection and to passive transfer of anti-HAV antibodies by blood transfusions.